Shear bond strength of adhesive systems to enamel and dentin. Thermocycling influence - Dos Santos, Patrícia Aleixo; Garcia, Patricia Petromilli Nordi Sasso [UNESP]; Palma-Dibb, Regina Guenka (Springer Nature, 2005)
Objectives: The purpose of the this study was to evaluate the influence of thermocycling on shear bond strength on bovine enamel and dentin surfaces of different adhesive systems. Methods: Thirty sound bovine incisors were sectioned in mesiodistal and inciso-cervical direction obtaining 60 incisal surfaces (enamel) and 60 cervical surfaces (dentin). Specimens were randomly assigned to 3 groups of equal size (n = 40), according to the adhesive system used: I-Single Bond; II-Prime & Bond NT/NRC; III-One Coat Bond. After 24-h storage in distilled water at 37 o C, each main group was divided into two subgroups: A- specimens tested after 24 h storage in distilled water at 37°C; B - specimens submitted to thermocycling (500 cycles). Shear bond strength tests were performed. Data were submitted to ANOVA and Tukey test. Results: Means (MPa) of different groups were: I-AE-16.96, AD-17.46; BE-21.60, BD-12.79; II-AE-17.20, AD-11.93; BE-20.67, BD-13.94; III-AE-25.66, AD-17.53; BE-24.20, BD-19.38. Significance: Thermocycling did not influence significantly the shear bond strength of the tested adhesive systems; enamel was the dental substrate that showed larger adhesive strength; One Coat Bond system showed the best adhesive strength averages regardless of substrate or thermocycling. © 2005 Springer Science + Business Media, Inc.
Keywords: Adhesives; Bond strength (chemical); Chemical bonds; Distillation; Surfaces; Thermal cycling; Adhesive systems; Bovine enamel; Mesiodistal; Enamels; water; adhesion; analysis of variance; animal tissue; chemical bond; dentin; enamel; incisor; material coating; nonhuman; priority journal; randomization; shear strength; storage temperature; surface property; temperature; Adhesiveness; Animals; Biocompatible Materials; Cattle; Dental Cements; Dental Enamel; Dentin; Incisor; Materials Testing; Periodicity; Shear Strength; Temperature; Bovinae